KUALITAS PELAYANAN KANTOR SAMSAT KABUPATEN TANA TORAJA - Muhammad Amar Pratama; Fatmawati Fatmawati; Abdi Abdi (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2022)
Public service is a form of service provided by the government to the community. Because in essence the government has the obligation and responsibility to provide good public services and can satisfy all parties. However, there are still people who complain about the services provided by SAMSAT in Tana Toraja Regency. The purpose of this study is to determine the service quality of the SAMSAT office in Tana Toraja Regency based on tangible, reliability, responsiveness, assurance, and empathy dimensions. This study uses a quantitative method that is descriptive. The data collection method used in this research is using a questionnaire. The data analysis technique used descriptive data analysis with the sampling method using the incidental sampling technique, namely anyone who happened to meet the researcher. The number of samples taken in this study were 89 people. The results showed that the service quality of the SAMSAT office in Tana Toraja Regency was based on tangible dimensions (90.7%), reliability (86.2%), responsiveness (87.2%), assurance (88.5%), and empathy (84). , 2%) obtained from the responses of 89 respondents were in the good category with a percentage of 87.5%.